2010
DOI: 10.3855/jidc.621
|View full text |Cite
|
Sign up to set email alerts
|

Activity of solvent extracts of Prosopis spicigera, Zingiber officinale and Trachyspermum ammi against multidrug resistant bacterial and fungal strains

Abstract: Background: The emerging trends of multidrug resistance among several groups of microorganisms against different classes of antibiotics led different researchers to develop efficient drugs from plant sources to counter multidrug resistant strains. This study investigated different solvent extracts of Prosopis spicigera (P. Spicigera), Zingiber officinale, and Trachyspermum ammi (T. ammi) to determine their efficacy against multidrug resistant microbes. Methodology: Successive extractions of these plants were p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
31
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 52 publications
(36 citation statements)
references
References 34 publications
4
31
1
Order By: Relevance
“…It was noted that the essential oil obtained by hydrodistillation presented strong antimicrobial activity, comparable to the concentrations reported in the range of micrograms per milliliter, compared to what has been reported as MIC and MBC for Streptococcus mutans, where apart from testing clove oil as an antimicrobial and anti-fungal for Candida albicans, a MIC and CMB of 390 and 780µg/mL, respectively, was demonstrated for Streptococcus mutans 22 . On the other hand, it has been reported that MIC of the essential oil of clove from India on Candida albicans varies from 1000 up to 2500µg/ ml, for Streptococcus sanguis was 0.31mg/mL.…”
Section: Discussionsupporting
confidence: 64%
“…It was noted that the essential oil obtained by hydrodistillation presented strong antimicrobial activity, comparable to the concentrations reported in the range of micrograms per milliliter, compared to what has been reported as MIC and MBC for Streptococcus mutans, where apart from testing clove oil as an antimicrobial and anti-fungal for Candida albicans, a MIC and CMB of 390 and 780µg/mL, respectively, was demonstrated for Streptococcus mutans 22 . On the other hand, it has been reported that MIC of the essential oil of clove from India on Candida albicans varies from 1000 up to 2500µg/ ml, for Streptococcus sanguis was 0.31mg/mL.…”
Section: Discussionsupporting
confidence: 64%
“…Candidemia is associated with considerable mortality. The management of Candida infections faces many problems, such as a limited number of antifungal drugs, toxicity, resistance of Candida to commonly used antifungal drugs, relapse of Candida infections, and the high cost of antifungal drugs [8,12]. It is therefore essential to discover new antifungal agents to combat strains expressing resistance to the available antifungal drugs.…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, the association of antibiotic use and the development of antibiotic resistance have been recognized as a cause of nosocomial and community-acquired infections. ESBLs, including TEM and SHV enzymes, [29] have been identified in Gramnegative bacteria such as K. pneumonia and E. coli; this adaptation has contributed enormously to the increased resistance to a broad range of antibiotics currently in use.…”
Section: Resultsmentioning
confidence: 99%